Sosialisasi Pencegahan Stunting melalui Bimbingan dan Konseling Kesehatan dan Gizi Anak Usia Dini di Desa Cipinang Kec. Cibatu Kab. Purwakarta - Kartika Sari; Irma Megawati; Miftachul Jannah; Dede Supendi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This research was conducted based on the results of observations and concerns experienced by the community. Stunting is one of the focus problems in Cipinang village which influences children's development as efforts to optimize stunting prevention take the form of child health and nutrition counseling through community service activities. The research method uses a Participatory Action Research (PAR) approach design. Starting with observing the problem, interpreting and analyzing it, then action is taken to alleviate the problems in society. Based on these Actions gradually understand the important role they play in maintaining children's Health. Apart from that, the community also has the potential to create broad social change because the community plays an active role in being collectively involved in jointly maintaining the health of children, preventing and alleviating stunting in Cipinang Village.